Who is an employee? From Theory to the Challenges of Technological Change - Polajžar, Aljoša (65 pravne znanosti v Mariboru, 2026)
This chapter of the monograph addresses the issue of the content and interpretation of criteria for determining the existence of an employment relationship in light of the technological changes brought about by platform work. In this chapter, the author primarily discusses the theoretical starting points of relevant domestic and foreign authors. To provide context for the discussion of the phenomenon of platform work, the author examines the case of the Uber ride-hailing platform (through some of the more relevant cases from the case law of supreme courts). The author concludes that, in light of the changes brought about by platform work, the content and interpretation of the criteria for determining the existence of an employment relationship for platform workers need to be updated. The absence of an obligation to perform work at a specific time is not an obstacle to determining the existence of an employment relationship.